Integrating a Global Learning Experience into an Inorganic Chemistry Teaching Laboratory - Grice, Kyle A.; Fraceto, Leonardo F. [UNESP] (American Chemical Society (ACS), 2020)
Science is a global endeavor, and as such, we as instructors should be training our students to see science through an international lens. However, for many students, studying abroad is often too costly or disruptive to degree progress. Therefore, other avenues of interaction with global science can provide similar enriching experiences to a wider range of students. As a part of a required undergraduate inorganic chemistry laboratory course in the United States and a standalone nanomaterials course in Brazil, the authors developed a virtual exchange in which students in both the United States and Brazil synthesized and characterized nanoparticles. Students also learned about nanotechnology and interacted with the students from the other country to discuss their data and do assignments related to nanotechnology. The challenges involved in creating and running such a Global Learning Experience Module in an inorganic chemistry laboratory will be discussed, as well as the Global Learning Experience content and suggestions for how other faculty may create such modules in their courses.